Surgical outcome of patients with Foramen Magnum Meningioma - Seddighi, Amir Saied (International Clinical Neuroscience Journal, 2015)
Purpose: In this study we aimed to investigate the benefits of far-lateral approach without partial condylectomy in patients with foramen magnum meningiomas over surgical approach with condylectomy. Methods: From 1980 to 2011, a total of 17 patients with foramen magnum meningiomas were treated surgically via far-lateral approach without condylectomy. The follow up period of this study was 6 to 24 months. Result: In this study, most of the tumor removals were done as complete resection. Operative deaths and significant complications were not noticed during procedure. Although all of the patients improved in their motor function, sensory deficits were resolved in 85% of patients by microsurgical far-lateral approach without partial condylectomy. Conclusion: Results of this study revealed that far-lateral approach without condylectomy is safe and effective in resection of foramen magnum meningiomas.